2021
DOI: 10.3389/fpsyg.2021.638618
|View full text |Cite
|
Sign up to set email alerts
|

Application of an Online Combination Exercise Intervention to Improve Physical and Mental Health in Obese Children: A Single Arm Longitudinal Study

Abstract: Introduction: Childhood obesity has become a global public health concern in the past decade. The purpose of this study was to explore the effectiveness of an online combination exercise intervention in improving the physical and mental health of obese children.Methods: This study adopted a one-group pre-test and post-test research design. A total of 28 obese children from 6 elementary schools in Heze City, Shandong Province, China, were recruited. All participants received an 8-week online combination exercis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
1
0
1
Order By: Relevance
“…Anteriormente, ya se habían mencionado las bondades de poder realizar sesiones en línea (Muellmann et al, 2018). Esta modalidad ha sido probada en distintos ámbitos, por ejemplo, módulos de aprendizaje de actividad física para pacientes con cáncer en un grupo de enfermeras de oncología (Karvinen et al, 2017), niños con obesidad (Ding et al, 2021) y niños con diabetes tipo I (Blake et al, 2016),…”
Section: Discussionunclassified
“…Anteriormente, ya se habían mencionado las bondades de poder realizar sesiones en línea (Muellmann et al, 2018). Esta modalidad ha sido probada en distintos ámbitos, por ejemplo, módulos de aprendizaje de actividad física para pacientes con cáncer en un grupo de enfermeras de oncología (Karvinen et al, 2017), niños con obesidad (Ding et al, 2021) y niños con diabetes tipo I (Blake et al, 2016),…”
Section: Discussionunclassified
“…In 2020, the new coronavirus swept the world, due to the rapid spread of the new coronavirus, infectious and other characteristics, people's traditional exercise methods are affected to a certain extent, the advantages of remote coaching exercise highlights, remote coaching exercise is not affected by time and space, can strengthen the body and improve the quality of life of people (Buneviciene et al, 2022;Dadswell et al, 2022;Han et al, 2022). Previous studies have shown that online combined exercise interventions are better for improving mental health and quality of life in obese children (Ding et al, 2021). There are also studies that confirm that teleexercise interventions improve muscle strength, cardiorespiratory endurance and mental health in breast cancer patients (Dong et al, 2018(Dong et al, , 2019(Dong et al, , 2020.…”
Section: Introductionmentioning
confidence: 99%